Blockchain Based Iot System to Monitor Indor Environment - Łukasz CZERNISZEWSKI (Communications of International Proceedings, 2024)
The article presents the design and implementation of a test stand aimed at monitoring and assessing the quality of the working environment in laboratory rooms. The proposed system integrates multiple Raspberry Pi microcomputers and environmental sensors to measure quantities such as temperature, humidity, pressure, light intensity, air quality and noise levels. These sensors continuously collect data on indoor environmental conditions, which is critical to ensuring compliance with health and safety standards, especially in hazardous materials laboratories. The system's distinguishing feature is the use of blockchain technology for secure, decentralized data exchange, ensuring immutability and transparency of data collected from sensors. Integration not only increases the reliability of data, but also enables effective audits to which the organization would be subject. Real-time monitoring capabilities enable proactive management of laboratory conditions, optimizing both worker safety and equipment performance. Potential applications include IoT-based environmental monitoring in laboratories, compliance with regulatory standards, and the development of decentralized data management for occupational health.
Keywords: IoT; Blockchain; Sensor-based environmental control systems; Indoor environmental quality (IEQ) in workspaces.